Strategi Badan Siber dan Sandi Negara dalam Mengatasi Permasalahan Judi Online Berdasarkan Perspektif Cyber Crime di Indonesia - Guntur Irawan; Amri Ramadhan (Social Issues Quarterly, 2023)
Advantages of Technology In addition to the positive impact, information can also have a negative impact, namely the possibility of being used to commit cyber crimes, such as online gambling. This descriptive research used qualitative method, which allows research to update information, so that knowledge can develop, be updated and produce information.to the public. Qualitative research is research that is descriptive in nature and usually uses inductive analysis. Process and meaning (subject perspective) are emphasized in qualitative research. Cyber ​​security is one area of ​​government that must be strengthened and advanced to achieve national flexibility, increase economic growth and ensure the implementation of government policies and programs in the field of cyber security. It is hoped that the formation of the BSSN will be able to answer the problems and challenges of the current and future cyber era and increase the commitment of the cyber security industry to deal with cyber threats in Indonesia. Management of cyber and crypto security human resources, cyber and crypto security policies or regulations, including the national cyber security strategy, cooperation and independence of cyber and crypto security in the context of implementing Indonesia's cyber sovereignty.